The giant within: A rare case of bilateral renal angiomyolipoma surpassing 30 cm - Hadj Hsain ihssan; Marrakchi salma; Laasri lina; Lahlou chaima; Boutaleb joud; Fenni Jamal; Ennouali Hassan (Radiology Case Reports)
We report the case of a 36-year-old woman who presented with abdominal distension and abdominal pain. Clinical examination revealed a significant increase in abdominal volume. A comprehensive biological workup was performed, including blood tests and tumor markers, followed by an abdominal CT scan. The imaging revealed 1 large retroperitoneal masses. To establish a definitive diagnosis, an ultrasound-guided biopsy was conducted, In this review, we evaluate our case of angiomyolipoma against others that have been documented in the literature by comparing its dimensions, clinic, course of therapy, complications, and evolution.